Mikrotik-based Hotspot Network Design Using the User Manager Authentification Method at SMKN 4 Bengkulu Selatan - Rahmat Al Ajwani; A.R Walad Mahfuzhi; Muntahanah; Khairullah (Penerbit Jurnal Indonesia, 2025)
Hotspot is a wireless internet access distribution media that has an authentication system for its users. Because with the hotspot system, internet access users are required to go through a network authentication stage by entering a username and password before being able to connect to the internet. Without systematic management, problems in hotspot services will occur very often. SMK N 4 Bengkulu Selatan has used an internet connection. However, the internet connection used has not been optimized, especially in terms of hotspot user management. This can cause several obstacles when accessing the internet, including the lack of security so that all users can access the internet only by entering the provided wifi password, the absence of user monitoring so that they do not know which hotspot users are active or inactive and the absence of bandwidth limitations for each user which results in unfair bandwidth usage often occurs. This study aims to design a hotspot network using Mikrotik devices with the implementation of the User Manager authentication method at SMK N 4 Bengkulu Selatan. The goal is to improve the security and management of internet access for users in the school environment. This study involves needs analysis, network topology design, and authentication protocol implementation. This method is expected to provide an effective solution in internet access management in educational environments.